Dry Eye Diseases and Ocular Surgery: Practical Guidelines for Canadian Eye Care Practitioners - Karpecki, Paul M.; Prokopich, C. Lisa; Racine, Louis; Bitton, Etty; Caffery, Barbara; Harasymowycz, Paul; Michaud, Langis; Pegado, Victor D.; Dufour, Jean-Sébastien; Neumann, Paul; et al. (Canadian Journal of Optometry, 2017)
In 2014, the Canadian Dry Eye Disease Consensus Panel published Guidelines for screening, diagnosis and management of dry eye diseases (DED). These did not address the implications of DED for individuals who are being considered for or have recently undergone ocular surgery. DED is common in certain surgical cohorts, and the perisurgical setting poses specific challenges, both because surgery can complicate preexisting DED and because symptomatic and non-symptomatic DED place the patient at risk of poor surgical outcomes. The Consensus Panel has developed this Addendum to the 2014 Guidelines to offer guidance on DED care before and after ocular surgery.